2022
DOI: 10.1080/20964129.2022.2052763
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen addition frequency and propagule pressure influence Solidago canadensis invasion into native plant community

Abstract: Introduction Propagule pressure (i.e., the number of propagules) has long been recognized to play an essential role in plant invasion. But it is not clear whether propagule pressure influences the invasion of exotic plants into native plant communities when different frequencies of nitrogen are added. Method We established an experiment with three plant communities that included native plant communities alone (four grasses, two legumes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Previous studies suggested that N levels can significantly affect the growth of S. canadensis ( Wan et al., 2018 ). The successful invasion of the exotic plant S. canadensis may be significantly affected by the N addition environment ( Liu X. S. et al, 2022 ). In this study, most plant growth- and development-related genes were differentially expressed in the N environment comparison groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that N levels can significantly affect the growth of S. canadensis ( Wan et al., 2018 ). The successful invasion of the exotic plant S. canadensis may be significantly affected by the N addition environment ( Liu X. S. et al, 2022 ). In this study, most plant growth- and development-related genes were differentially expressed in the N environment comparison groups.…”
Section: Discussionmentioning
confidence: 99%
“…A stability may exist for the community assembled by the alien invader and native plants since the community could "tolerate" the environmental perturbation from N deposition and AMF inoculation (Ghedini and Connell, 2016). Previous studies on the effects of environmental perturbation on the invasibility of native plant community showed two contrast paradigms including: 1) the invader up and the native down, in which the invasion process strengthens; and 2) the invader down and the native up, in which the biotic resistance strengthens (Liu et al, 2018;Zheng et al, 2020;Gao et al, 2021;Wang et al, 2021;Jin et al, 2022;Li et al, 2022b;Liu et al, 2022). However, the present study tends to show a balance between the alien invader and native plant community, especially considering the phenotypic maintenance of alien invader.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, biological invasion has been shown to have detrimental ecological effects such as the exclusion of native species and the alteration of community structure (Zhang and van Kleunen, 2019). Importantly, plant invasion success can be mediated through background nitrogen deposition across a range of different ecosystems (Valliere et al, 2017;Wang et al, 2021;Liu et al, 2022;Wang et al, 2022). Indeed, the resource fluctuation hypothesis predicts that N deposition may enhance the habitat resource availability and improve their hospitability for plant invasion (Davis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation